PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN KREATIVITAS PESERTA DIDIK KELAS IV SDN KUTOWINANGUN 01 SALATIGA SESUAI GAYA BELAJAR - Via Putika Sari; Wahyudi Wahyudi (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2023)
The purpose of this study is to increase creativity by implementing a Recovery Learning model which is adjusted to the learning style of students in the IVC class SDN Kutowinangun 01 Salga. The type of research used is a collaborative class (PTKK) study with spiral models of Stephen Kemmis and Robin Mc. Taggart consisting of three stages is planning, implementation and observation, and reflection. Data collection techniques use observation and documentation. Data collection instruments used are in the form of observation sheets of students’ creativity and documentation impelementasi model Covered Learning (DL). Data analysis techniques using comparative descriptive analysis by comparing the creativity of students from cycle 1 to cycle 3. The results showed that the average creativity of students at a cycle of 1 only 46% categorized as low creativity, to the 3 cycle of an increase to 76% which is included in the high creativity category. The frequency of students with a high creativity category at the 1 cycle of 5 students (22% of 23 students), then the 3 cycle increases to 18 students (78% of 23 students). Thus, it can be known that the model is covered learning can increase the creativity of students. Through this study, it is hoped that teachers can increase the creativity of students by prioritizing active involvement in finding themselves the concept of the material learned so that students can take meaning both of each learning step followed.